Legal Status of Marriage Contract Deeds Made Before a Notary Without Registration at a Marriage Registration Office - Hernawan, Faisal Abdillah (Jurnal Konstatering, 2024)
This research aims to determine the legal status of marriage agreement deeds made before a notary without being registered at the Marriage Registration Office as well as the legal impact for third parties of marriage agreements made before a notary without being registered at the Marriage Registration Office if a dispute occurs. The type of research is qualitative with a statutory approach. Data collection techniques are documentation, observation and literature study. This type of research is a normative approach or doctrinal research which is oriented towards approaches to various statutory and regulatory norms. The research results show that 1) the legal position of a marriage agreement deed made before a notary without being registered at the Marriage Registry Office is that the agreement remains valid and binding for husband and wife, but does not have binding legal force on third parties. 2) A marriage agreement made before a notary but not registered at the Marriage Registry Office does not have binding legal force on third parties. The legal consequence is that third parties are not bound by the agreement and can assume that the assets of the husband and wife are joint assets. In the event of a dispute or debt, a third party can demand a settlement involving the couple's joint assets, because there is no legally recognized separation of assets.